2016
DOI: 10.1111/joim.12458
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics and epigenetics of nonfamilial (sporadic) parathyroid tumours

Abstract: Primary hyperparathyroidism (pHPT) is a common endocrine disease characterized by excessive secretion of parathyroid hormone and an increased level of serum calcium. Overall, 80–85% of pHPT cases are due to a benign, single parathyroid adenoma (PA), and 15% to multiglandular disease (multiple adenomas/hyperplasia). Parathyroid carcinoma (PC) is rare, accounting for <0.5–1% of pHPT cases. Secondary hyperparathyroidism (sHPT) is a complication of renal failure, with the development of parathyroid tumours and hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…PCs (approximately 70%), and parafibromin-negative immunostaining has been suggested as a marker for PC, although some studies reported this to be less useful (Tan et al 2004, Iacobone et al 2005, DeLellis et al 2008, Sharretts & Simonds 2010, Guarnieri et al 2012, Cetani et al 2013, Gill 2014, Westin 2016. Lost expression of the APC tumor suppressor gene has been suggested to occur in PCs through epigenetic inactivation by DNA methylation of the APC promoter region (Svedlund et al 2010).…”
Section: :7mentioning
confidence: 99%
“…PCs (approximately 70%), and parafibromin-negative immunostaining has been suggested as a marker for PC, although some studies reported this to be less useful (Tan et al 2004, Iacobone et al 2005, DeLellis et al 2008, Sharretts & Simonds 2010, Guarnieri et al 2012, Cetani et al 2013, Gill 2014, Westin 2016. Lost expression of the APC tumor suppressor gene has been suggested to occur in PCs through epigenetic inactivation by DNA methylation of the APC promoter region (Svedlund et al 2010).…”
Section: :7mentioning
confidence: 99%
“…Wnt/β-catenin is potentially deregulated in PCas by loss of parafibromin, which is a member of the polymerase II complex interacting with β-catenin [36]. Therefore, Wnt/β-catenin deregulation has been suggested as a “hub” of parathyroid tumorigenesis [37] (Figure 1). Indeed, accumulation of β-catenin is controversial in PCas, with studies reporting constitutive accumulation of active unphosphorylated β-catenin [26] and others failing in the detection of total β-catenin at the nuclear level [38].…”
Section: Dna Methylation In Parathyroid Cancersmentioning
confidence: 99%
“…Schematic representation of the molecules involved in the Wnt/β-catenin signaling in the inactive (left) and active (right) state: molecules, whose expression may be affected by genetic and epigenetic modifications in PCas, are indicated. The Wnt/β-catenin deregulation has been suggested as a “hub” of parathyroid tumorigenesis [37]. DKK1, Dickkopf 1; DVL, disheveled segment polarity protein; SFRP, secreted frizzled related protein; CKI, cyclin-dependent kinase inhibitor; GSK3, glycogen synthase kinase 3 β; TCF/LEF1, transcription factor 7/lymphoid enhancer binding factor 1; HIC1, hypermethylated in cancer 1; WT1, Wilms tumor 1; RASSF1A, Ras-association domain family 1; LRP-5, low density lipoprotein (LDL) receptor related protein 5; LRP-6, low density lipoprotein (LDL) receptor related protein 6; CDC73, cell division cycle 73; APC, WNT signaling pathway regulator; WNT, wingless-type ; ub, ubiquitination; ⊥, inhibitory effect.…”
Section: Figurementioning
confidence: 99%
“…These mutations are commonly found in young patients with clinically non-familial PHPT (Starker, et al 2012). Other parathyroid tumors may be due to activation of the WNT/β-catenin signaling pathway (Westin 2016). Inactivating mutations of the CDC73 tumor suppressor gene have been reported in hyperparathyroidism–jaw tumor (HPT–JT) syndrome-related adenomas and parathyroid carcinomas, in association with the loss of nuclear expression of the encoded protein, parafibromin.…”
Section: Vagal Parathyroid Tumorsmentioning
confidence: 99%